Stigmatization of Pregnant Individuals with Opioid Use Disorder - Allison D. Crawford; Kelly McGlothen-Bell; Pamela Recto; Jacqueline M. McGrath; Leticia Scott; Elizabeth A. Brownell; Lisa M. Cleveland (Mary Ann Liebert, 2022)
Objective: The purpose of this study was to critically analyze the role of stigma in the care of pregnant and parenting individuals with opioid use disorder (OUD) through the theoretical lens of the Reproductive Justice (RJ) framework. Background: Overdose related maternal mortality, often involving opioids, is a national growing public health concern. OUD is a highly stigmatized condition that may negatively influence the well-being of pregnant/parenting individual's reproductive and human rights. Study Design: Secondary qualitative data analysis. Methods: A secondary data analysis was conducted using individual interviews (N?=?23) from a larger study aimed at examining contextual factors surrounding pregnant/parenting individual's experiences with opioid use return to use and/or overdose. The RJ framework was used as a framework to examine the influence of OUD-related stigma and a person's right to bodily autonomy, their right to parent, and their right to parent the children they have in safe and sustainable environments. Results: The RJ framework supported the examination of factors that perpetuate stigma in this population. Individuals described stigmatizing experiences in the health care setting. Verbal and nonverbal interactions with health care providers and fear of child welfare involvement were counterproductive to recovery and potentially triggered OUD recurrence and/or overdose. Conclusions: Due to existing stigma, pregnant and parenting individuals with OUD often avoided health care and recovery support services; therefore, there should be the removal of barriers that prevent this population from accessing life-saving services. Future efforts should focus on health policy-related research to support structural changes within institutions.